Effort to Control Pulmonary Tuberculosis (TB) in the Community through Tuberculosis Alert Health Cadre Training - Yogi Fitriadi (Journal of Community Empowerment for Health, 2023)
Tuberculosis (TB) alert health cadre training is an important thing that can be done to help control TB in the community. TB control includes increasing early detection and adherence to treatment for TB patients. To solve TB problems in the community, a synergy of roles is needed between health workers and the community, one of which is through empowering health cadres by increasing their capacity. We conducted interactive TB control health education training program that aim to improve health cadre knowledge, attitudes, and practice in early detection of TB and assistance to Drug Swallowing Supervisors/”Pengawas Menelan Obat (PMO)”. The training was provided using lecture method, two-way discussion, and demonstration for one day by internal medicine specialists, assisted by multi-professional students from medical and nursing program. A total of 36 health cadres from Sumberharjo village participated in this training. Before and after the training, cadres took pre-test and post-test. The survey results were analyzed statistically using descriptive quantitative methods for the respondent’s characteristics, whereas the score of knowledge, attitude, and practice were analyzed using nonparametric test. The median and the minimum-maximum of the pre-test score before training for knowledge was 10.5(7-13), attitude score was 15(11-15), and practice score was 15(8-15). Meanwhile, the median and the minimum-maximum post-test score after training for knowledge was 11(8-14), attitude score was 15(10-15), and practice score was 15(10-15). The results of statistic test obtained were p=0.003 for knowledge, p=0.272 for attitude, and p=0.111 for practice. It showed that there was a significant difference in the cadre's knowledge scores before and after training, but there were no significant differences in their attitudes and practice scores before and after training. Training for health cadres is recommended to increase capacity of health cadre, especially the knowledge of health cadre controlling TB in the community.